Experimental Study on the Effect of Water on the Properties of Cast In Situ Foamed Concrete - Wenhui Zhao; Qian Su; Wubin Wang; Lele Niu; Ting Liu (Advances in Materials Science and Engineering, 2018)
This study aims to investigate the effect of water on the properties of cast in situ foamed concrete with a dry density of 300–800 kg/m3 (100 kg/m3 is a gradient). Firstly, the shrinkage deformation with the curing time and the volumetric moisture content is studied by the drying shrinkage test and improved drying shrinkage test. Secondly, the influence of volumetric moisture content on mechanical properties is assessed. At last, the effects of immersion time and immersion type on the mechanical properties of foamed concrete are studied by considering the water-level conditions. The achieved results show that the shrinkage deformations increase with the curing time for the drying shrinkage test and the improved drying shrinkage test, while the variations are different. The shrinkage deformation increases with the decrease of volumetric moisture content for six dry densities of foamed concrete. Besides, it gradually changes in the early stage, while it changes fast in the later stage. The compressive strength and elastic modulus decrease with the increase of volumetric moisture content for each density. For the water-level unchanged condition, the compressive strength and elastic modulus initially decrease and then slowly increase with the increase of the immersion time. For the water-level changed condition, the compressive strength and elastic modulus of foamed concrete decrease with the increase of immersion time for each dry density, and the rate of early attenuation is high, whereas the rate of later attenuation is limited.